The Political Economy of Extreme Poverty in Eastern Europe: A Comparative Historical Perspective of Romanian Roma - Enikő Vincze; Cornel Ban; Sorin Gog; Jon Horgen Friberg (Routledge, 2025)
This book examines the creation of extreme poverty in Eastern Europe, focusing on Romanian Roma, through a comparative historical perspective on its roots and the socio-economic and political mechanisms that have shaped it in labor, housing, and migration. This interdisciplinary book explores the (re)production of extreme poverty among the Roma across different political economy regimes. Chapters engage in comparative historical analysis across several disciplines and integrate perspectives steeped at the national level of analysis with those dwelling intensively on a single context. Focusing on the processes of manufacturing poverty among Roma in Romania, the chapters cover empirical information about the historical transformations of the economic situation of the Roma in Romania from the 19th century to the present, about global, national, and local processes of industrialization, deindustrialization, and reindustrialization impacting poverty among the Roma in the past seven decades, and about Roma people's current labor positions, housing conditions, and migration practices in distinct geographies from Romania to Norway. The book situates Roma poverty research in a Central and Eastern European context by highlighting its connections with analytical approaches to poverty and institutional policy visions about poverty eradication. It will be of interest to researchers studying Central and Eastern Europe, political economy of socialism, political economy of capitalist transformations, poverty studies, welfare and housing regimes studies, and labor and migration studies.
Keywords: 940; Roma; Manufacturing Poverty; socio-economic situation; political economy; welfare and housing regimes; labor and migration studies; social history